Microbe-mineral interactions in the Plastisphere: Coastal biogeochemistry and consequences for degradation of plastics - Dodhia, Maya S.; Rogers, Kelsey L.; Fernández-Juárez, Victor; Carreres-Calabuig, Joan A.; Löscher, Carolin R.; Tisserand, Amandine A.; Keulen, Nynke; Riemann, Lasse; Shashoua, Yvonne; Posth, Nicole R. (Frontiers in Marine Science, 2023)
Microbe-mineral interactions, such as mineral substrate utilization and aggregate formation, have played a key role in the cycling of elements through Earth evolution. Plastic, by contrast, is a new material with roots in the 20th century that is now widespread in the environment. In water, soils, and sediment, e.g., of coastal marinas, microorganisms colonize and minerals precipitate on and around plastic of all sizes. Importantly, in such aquatic environments, the surrounding biogeochemistry modulates microbial community composition and mineral formation over spatial and temporal scales. Both microbial and mineral associations with plastic comprise the Plastisphere, which influences the fate of plastic. This study focuses on how the biogeochemical environment defines microbial and mineral association with polyethylene (PE) and polystyrene (PS) over a 12-month period in a temperate coastal harbour. Here, the coastal harbour environment was separated into 3 conceptual compartments defined by physical and biogeochemical conditions, e.g., light penetration and redox conditions that allow transfer of electrons between species. Microbe and mineral association were investigated in the water column, top sediment (water-sediment interface to 4 cm depth), and bottom sediment (4 to 20 cm depth) using a range of analytical techniques to identify changes in the chemical structures of plastics, microbial community development, metal, salt and mineral formation applying a range of modern analytical techniques. The epiplastic microbial community was found to be distinct to that of the surrounding environment across changing redox conditions in the water column, top sediment and bottom sediment. The type and oxidation state of metallic minerals formed on plastics or entrapped in the biofilm matrix related to dominant abiotic and biotic processes in shifting redox conditions. FTIR spectroscopy indicated the occurrence of oxidation of PE and PS in the various biogeochemical environments. Combined, these findings demonstrate that redox conditions and surrounding biogeochemistry drive the composition of mineralogical and biological loading of PE and PS in coastal marine environments over time. In turn, this suggests that the biogeochemical setting in which the plastics are stored constrains the development of plastic interfacial biogeochemistry and the potential for plastic degradation and transport over time.